2015
DOI: 10.1111/cid.12322
|View full text |Cite
|
Sign up to set email alerts
|

An Up to 12‐Year Retrospective Follow‐Up on Immediately Loaded, Surface‐Modified Implants in the Edentulous Mandible

Abstract: Immediate loading of surface-enhanced implants is a highly predictable and successful treatment modality in the edentulous mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
(124 reference statements)
1
6
0
Order By: Relevance
“…In the present study, immediate loading in the lower jaw with 5 fluoride‐modified implants showed a survival of 100%. This is in accordance with other studies describing a high implant survival (91%‐100%) and prosthetic survival (96.4%‐100%) with 1‐ to 6‐year follow‐up . The bone loss after 10 years in function with implant installation as baseline was 0.50 mm (range 0–7.8).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, immediate loading in the lower jaw with 5 fluoride‐modified implants showed a survival of 100%. This is in accordance with other studies describing a high implant survival (91%‐100%) and prosthetic survival (96.4%‐100%) with 1‐ to 6‐year follow‐up . The bone loss after 10 years in function with implant installation as baseline was 0.50 mm (range 0–7.8).…”
Section: Discussionsupporting
confidence: 91%
“…and D.M. ), and the collected information was tabulated according to (1) reference; (2) study design; (3) demographic data; (4) study groups;…”
Section: Data Extractionmentioning
confidence: 99%
“…Dental implants are a modern substitute for dentures for patients with missing teeth. Studies have shown that dental implants can remain esthetically and functionally stable for prolonged durations in a manner similar to natural teeth. Periodontal and peri‐implant disease are inflammatory conditions associated with the soft (gingivae) and hard (alveolar bone) tissues surrounding teeth and dental implants, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking shows an overwhelmingly negative influence on oral health, affecting both soft and hard tissues. It is known as an important risk indicator for poor oral wound healing, dry socket, implant failure, and marginal bone loss around teeth and implants [5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In regard to dental implants, a significant relationship has been shown between smoking and the risk of failure of osseointegrated implants, more particularly in the upper jaw [8,24].…”
Section: Introductionmentioning
confidence: 99%